DIVIDING THE PIE – DEALING WITH SURPLUS AND DROUGHT: EXAMINING THE COLORADO RIVER COMPACT OF 1922 (Utah Environmental Law Review, 2009)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} As the Southwest endures a sixth year of record drought, it should come as no surprise that many water managers, public officials and water use stakeholders alike are examining the Colorado River Compact of 1922, and asking the question, “Is it time for change?” From my personal perspective—and from that of every Administration to serve from 1922 to the present, a span of eighty-five years—there is no compelling case to change the Compact. It’s long been my belief that the Compact was an inspired gift to future generations hammered out under extremely difficult circumstances. It represents the best of what happens when the seven Basin States and the Federal Government sit down to work for the common good. Is the Compact perfect?   Did everyone get an equal deal?   Of course not.   Is it flexible?   Is there room for evolving issues and the various states’ needs to be met?   Absolutely!